Alpha-lipoic acid and mesuagenin c-induced co-regulation of nf-κβ-cytokines and chemokines via pi3k-akt/gsk-3β and erk1/2 in in vitro neuronal models / Muhamad Noor Alfarizal Kamarudin - Muhamad Noor Alfarizal , Kamarudin (2016)
(R-)(+)-α-lipoic acid and mesuagenin c were shown to protect the NG108-15 cells against H2O2-induced cell death by mitigating the caspase-dependent mitochondrial-mediated pathway. (R)-(+)-α-lipoic acid activated both mTORC1 and mTORC2 components whereas mesuagenin c only activated mTORC2 component which led to activation of PI3K-Akt pathway. This was followed with the reduction of both Bax/Bcl2 and Bax/Bcl-xL ratios and inhibition of cleaved caspase-3. Both compounds suppressed the NF-κB p65 nuclear translocation by inactivating the GSK-3β which reduced IL-6 and TNF-α by increasing the production of IL-10. Following H2O2 exposure, the level of CCL21 was significantly increased and pretreatment with both compounds decreased the CCL21 level in NG108-15 cells. Since both compounds modulated the co-regulation of NF-κB, cytokines and chemokine, therefore their anti-neuroinflammatory properties and mechanisms against LPS-stimulated BV-2 cells co-cultured with NG108-15 cells were investigated. Pretreatment with both compounds increased the BV-2 cells viability and inhibited both inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). This was followed with attenuation of nitric oxide, intracellular reactive oxygen species (ROS) and prostaglandin E2 level. Cytokines protein array revealed that both compounds displayed different efficacy in suppressing the production of anti- and pro-inflammatory chemokines and cytokines. Furthermore, both compounds attenuated the production of Galectin-3 which is required for resident microglia activation. Pretreatment with (R)-(+)-α-lipoic acid and mesuagenin c activated the PI3K-Akt which inactivated GSK-3β(Ser9) and subsequently suppressed NF-κB p65 translocation. Moreover, the addition of lithium chloride and API-2 significantly reversed LPS-induced pro-inflammatory cytokines and chemokines production which accentuated the importance of PI3K-Akt/GSK-3β pathway in modulating NF-κB, cytokines and chemokines co-regulation. Following CCL21 knockdown, both transfected and wild-type NG108-15 co-cultured with BV-2 cells which were pretreated with both compounds displayed suppression of microglial inflammation. Moreover, The knockdown-CCL21, (R)-(+)-α-lipoic acid- and mesuagenin c-microglia conditioned media improved neuronal viability and mitigated neuronal cells death which suggested that downmodulation of CCL21 is crucial in suppressing microgliosis-induced neuronal cell death. Additionally, mesuagenin c induced neuritogenesis by activating of PI3K-Akt and ERK1/2 pathways which increased the neurofilament protein (-70, 150 and 200 kDa) expression. The neuritegenesis observation was abolished following the addition of API-2, UO126 and Wortmannin inhibitors. Interestingly, mesuagenin c modulated the production CCL21, Galectin-1 and other pro-inflammatory cytokines and chemokines as compared to control and inhibitors-treated cells. However, pretreatment with Pertussin Toxin significantly abolished neuritogenesis highlighting the importance of chemokines in neuritogenesis. Following knockdown of CCL21, mesuagenin c-induced neuritogenesis through production of cytokines was reduced as compared to recombinant CCL21-treated cells which suggested CCL21 potential novel role in neuritogenesis. Aberrant co-regulation of NF-κB, cytokines and chemokines is detrimental in neuronal system. Nevertheless, this paradoxical finding may suggest otherwise and merit further investigation of mesuagenin c and CCL21 roles which coincides with its both anti- and pro-inflammatory mechanisms. Taken together, these findings exemplify the natural products ability to modulate NF-κB, chemokines and cytokines reciprocal regulation via PI3K-Akt/GSK-3β and ERK1/2 pathways.